PENINGKATAN KUALITAS PELAYANAN PUBLIK PADA RUMAH SAKIT UMUM DAERAH KOTA TARAKAN - Meidi Priandana; Dan Buntu Paranoan; Achmad Djumlani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Tarakan Hospital Regional Public Health Office has a duty, powers and functions in the field of public health services. With the increasing complexity of health problems in the world and the increasingly high demand, the demand for health services Tarakan Hospital is required to work on improving the quality of health care as one of improving public health efforts. The results of this study recommend some strategic issues that ought to be implemented by the Tarakan Hospital are required to work on improving the quality of health services to the community. Strategic issues which should be developed by the Tarakan Hospital is utilization of advances in technology, improve and maximize Human Resources and optimization of existing facilities